(untitled) (World Economics and Finance Bulletin, 2026)
In recent years, digital transformation has emerged as a fundamental driver of innovation across financial and accounting systems. The present study examined the impact of digital innovations and Accounting Information Systems on the enhancement of internal audit quality and supervisory functions at Rafidain Bank. The research used a qualitative, sequential exploratory design. The statistical population comprised senior executives, board members, and subject-matter experts with substantial domain familiarity, and participants were selected through purposive and snowball sampling. Data were collected through in-depth semi-structured interviews and participant observation, and subsequently analyzed using open, axial, and selective coding procedures. The findings indicated that technological infrastructure development, digital maturity, employee empowerment, supportive leadership, and an innovationoriented organizational culture were key determinants of improved audit quality and financial information transparency. Moreover, technologies such as blockchain, data analytics, and artificial intelligence played a significant role in enhancing accuracy, reducing errors, and strengthening accountability. The results further demonstrated that digital transformation not only improved internal monitoring and control mechanisms but also contributed to increased trust, operational efficiency, and organizational value creation.